Gambaran Tingkat Kemandirian Lansia dalam Pemenuhan Activities of Daily Living (ADL) di Rumah Pelayanan Sosial Lanjut Usia Pucang Gading Semarang - Nada Darmawan; Iskim Lutfha; Moch Aspihan; Abrori Abrori (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2025)
The World Health Organization (WHO) defines elderly as someone who has reached the age of 60 years and over. Decreased musculoskeletal function causes a decrease in the elderly's ability to carry out daily living activities. The elderly's ability to carry out ADL activities of daily living will illustrate the elderly's independence in daily activities. If the elderly cannot fulfill ADL independently then the elderly experience ADL disorders. The purpose of this research to find out the description of the level of independence of the elderly in fulfilling the Activities of Daily Living (ADL) at the Pucang Gading Semarang Elderly Social Services Home. This type of research is quantitative research, with a descriptive research design. The sampling technique used a total sampling method of 111 respondents with inclusion criteria: a.) Elderly people who are communicative b.) Elderly people who are willing to be respondents without coercion. The data collection method used the Katz ADL Index questionnaire. The data analysis used is univariate analysis to find the frequency distribution of each data. The results of this research show that Characteristics: The majority of respondents were female, 63 respondents (56.8%), while the majority aged 60-74 years were 74 respondents (66.7%). Meanwhile, the level of independence of the elderly, measured by the Katz Index, shows that the majority do Bathing and Dressing independently with a total of 98 elderly people (88.3%), Toileting independently with a total of 94 elderly people (84.7%), Transferring independently with a total of 67 elderly people (60.4%), and for independent Continence there are 79 elderly people (71.2%). This shows that the majority of respondents have a level of independence, 56 respondents 50.5%. (11.7%). Characteristics: The majority of respondents are women, the majority are aged 60-74 years, and the level of independence of the elderly is that the majority are independent